2016
DOI: 10.1186/s12936-016-1167-z
|View full text |Cite
|
Sign up to set email alerts
|

Clinical trials of artesunate plus sulfadoxine-pyrimethamine for Plasmodium falciparum malaria in Afghanistan: maintained efficacy a decade after introduction

Abstract: BackgroundCombination therapy with artesunate plus sulfadoxine-pyrimethamine (SP) was adopted as recommended treatment for Plasmodium falciparum infection in Afghanistan in 2003.MethodsA series of prospective clinical studies examining the efficacy of artesunate plus sulfadoxine-pyrimethamine (AS + SP) against P. falciparum were undertaken in sentinel sites in Afghanistan from 2007 to 2014, accompanied by relevant molecular studies. The first study was a randomized trial of AS + SP versus dihydroartemisinin-pi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 31 publications
2
5
0
Order By: Relevance
“…Moreover, a therapeutic efficacy study conducted in Zhob, Kech, Khairpur, Thatta, Khrram agency, and Khyber agency also reported near fixation of the PfDHFR double mutant [22]. Similar results have also been reported in the neighboring countries of Iran [34], Afghanistan [35], India [36] and China [37].…”
Section: Discussionsupporting
confidence: 56%
“…Moreover, a therapeutic efficacy study conducted in Zhob, Kech, Khairpur, Thatta, Khrram agency, and Khyber agency also reported near fixation of the PfDHFR double mutant [22]. Similar results have also been reported in the neighboring countries of Iran [34], Afghanistan [35], India [36] and China [37].…”
Section: Discussionsupporting
confidence: 56%
“…Currently, nine countries recommend AS + SP as their first‐line treatment (Afghanistan, Djibouti, India, Islamic Republic of Iran, Pakistan, Saudi Arabia, Somalia, Sudan and Yemen). Recent evidence has shown that AS + SP treatment was failing in north‐east India, leading to its subsequent replacement , while high cure rates (> 95% ACPR) of the combination have been reported in Yemen and Afghanistan .…”
Section: Discussionmentioning
confidence: 99%
“…Patients were censored from analysis if there was stated withdrawal of consent, severe malaria or persistent vomiting during the acute phase (necessitating parenteral treatment) or development of concomitant disease interfering with classification of treatment outcome. Patients who developed P. falciparum infections were treated with artesunate plus sulphadoxine-pyrimethamine 16 and retained in the study. Patients failing to attend follow-up were visited at home and asked to reattend the center.…”
Section: Methodsmentioning
confidence: 99%